An Exploratory Study on the Validation of Lehman’s Laws - Sousa, Augusto Braz De; Pessoa Neto, Izaias; Ferreira, Fischer (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Considering the changing and constantly evolving environment of information systems development, marked by technological advancements, the relevance of Lehman’s eight laws becomes apparent. Problem: Uncertainty regarding the ongoing relevance of Lehman’s laws in contemporary information systems. Solution: This study aims to obtain indications about the validity of Lehman’s Laws by analyzing the evolution of three information systems. SI Theory: This study is conceived from the General Systems Theory (GST) perspective when analyzing laws for the evolution of information systems. The integration of these perspectives provides a foundation for analyzing information system evolution guiding eﬀective management strategies. Method: The research follows an exploratory empirical approach comprising four stages: i) Application of the GQM framework to validate Lehman’s Laws; ii) Data collection using metrics applied to the target information system; iii) Data preparation and metric processing; iv) Quantitative analysis, examining metrics across diﬀerent versions of the systems. Summary of Results: The results highlight that Lehman’s eight laws were examined and validated, two partially, in the context of the information systems covered in this study. Contributions and Impact on the IS Field: This study contributes to understanding the evolution of information systems, emphasizing the practical application of Lehman’s Laws. The results will be valuable in providing a more profound understanding for researchers and professionals interested in the evolution of information systems.